HUBUNGAN KUALITAS, SISA MAKANAN, DAN TINGKAT KEPUASAN TERHADAP LAYANAN MAKANAN PADA PASIEN RAWAT INAP RUANG ANAK KELAS III DI RSUD KOJA - Cindi Ingan Malem Sembiring; Agustina Indri Hapsari; Widartika; Dadang Rosmana; Azzahra Nadya Putri (Jurnal Gizi dan Dietetik, 2026)
Hospital foodservice plays a crucial role in meeting patients' nutritional needs and supporting the healing process. However, poor food quality may lead to increased plate waste and decreased patient satisfaction. This study aimed to determine the relationship between food quality and plate waste with food service satisfaction among Class III pediatric inpatients at Koja Regional General Hospital. A cross-sectional design was used with 79 respondents. Food quality and patient satisfaction data were collected using questionnaires, while plate waste was measured using the visual Comstock method. Data were analyzed using the Spearman correlation test. The results showed that food quality was generally rated as good, with appearance (83.5%), taste (79.7%), and variety (86.1%) being the most positively rated aspects. The highest plate waste was found in vegetables (62.0%) and plant-based side dishes (49.4%). Patient satisfaction with foodservice was high (97.5%). Spearman correlation analysis revealed a strong and significant positive relationship between food quality and patient satisfaction (r = 0.678; p = 0.000). However, there was no significant relationship between plate waste and patient satisfaction (r = -0.203; p = 0.073). Further studies are recommended to explore food waste based on food category.